HYDROCEPHALUS AND CRANIOSYNOSTOSIS IN PAEDIATRICS: COEXISTENCE OF TWO PHENOMENA - Permana, Khrisna Rangga; Parenrengi, Muhammad Arifin; Suryaningtyas, Wihasto (Journal of Ayub Medical College Abbottabad, 2024)
Background: Here, the authors describe their institutional experience managing patients who had hydrocephalus and craniosynostosis regarding their pre-operative and post-operative data. Methods: The study was conducted in the Neurosurgery Department, Dr. Soetomo Academic General Hospital, Surabaya, Indonesia. Four patients with craniosynostosis had hydrocephalus based on our database and all of those four cases were reviewed. The authors retrospectively reviewed the patient’s demography, clinical findings, radiology results, operative procedures, and complications after surgery. Results: Four patients underwent the cerebrospinal fluid (CSF) procedure and survived the procedure. Three patients were operated at the first 1 year of age and one patient at 2 years old. There were no major complications (sepsis, reoperation, death) postoperatively. Conclusion: The mechanism of the hydrocephalus in craniosynostosis was not fully elucidated. Suspicion of hydrocephalus should be anticipated in every case of craniosynostosis and further examination such as a CT scan was necessary. In the setting of progressive ventriculomegaly, a CSF diversion should be performed. d.